2023
DOI: 10.1111/jan.15974
|View full text |Cite
|
Sign up to set email alerts
|

Implementation leadership of the Resident Assessment Instrument in healthcare services for older people: An interview study of specialists

Suvi Kuha,
Pia Vähäkangas,
Outi Kanste

Abstract: AimThe aim was to explore implementation leadership of the Resident Assessment Instrument in healthcare services for older people from the perspective of specialists.DesignA qualitative descriptive design was used.MethodsThematic interviews with 21 specialists were conducted between April 2022 and June 2022 in eight health and social, one educational and one research organization in Finland. The data were analysed with deductive–inductive content analysis using the Resident Assessment Instrument implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous attempts to use such MDSs in UK research studies found low completion rates and crucially, a higher burden associated with staff completing them on top of existing data requirements [57,58]. The work of implementation for uptake and sustained use is as significant and arguably more resource intensive than we found for our prototype dataset[59].…”
Section: Discussionmentioning
confidence: 82%
“…Previous attempts to use such MDSs in UK research studies found low completion rates and crucially, a higher burden associated with staff completing them on top of existing data requirements [57,58]. The work of implementation for uptake and sustained use is as significant and arguably more resource intensive than we found for our prototype dataset[59].…”
Section: Discussionmentioning
confidence: 82%